The use of treated brewery effluent as a water and nutrient source in crop irrigation - Taylor, Richard Peter (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Brewery effluent (BE) needs to be treated before it can be released into the environment, reused or used in down-stream activities. Current technologies used to address this concern at the experimental wastewater treatment plant at Ibahyi Brewery (SAB Ltd) include anaerobic digestion (AD), primary facultative ponds (PFP), high rate algal ponds (HRAP) and constructed wetlands (CW). The aim of this work was to determine if BE treated in these systems might be suitable for crop irrigation. A test crop, cabbage (Brassica oleracea cv. Star 3301), grew best on post-AD and post-PFP BE compared to those irrigated with post-HRAP or post-CW effluent. However, the yield was 13% lower than cabbage plants irrigated with a commercial nutrient solution and fresh water. The relatively high conductivity (3019.05 ± 48.72 μs/cm2) of BE may be the main factor reducing the cabbage yields. Post-HRAP and post-CW BE were the least suitable for irrigated crop production due to the higher conductivity and lower nutrient content of these treated effluents. After three months, soils irrigated with post-AD and post-PFP BE had a significantly higher sodium content and sodium adsorption ratio (3919 ± 94.77 mg/kg & 8.18 ± 0.17) than soil irrigated with a commercial nutrient solution (920.58 ± 27.46 mg/kg & 2.20 ± 0.05; p<0.05). However, this was not accompanied by a deterioration in the soil's hydro-physical properties, nor a change in the metabolic community structure of the soil (p>0.05). After prolonged irrigation with treated BE, sodium is likely to build up in the soil and this can be expected to be accompanied by a deterioration in the soil physical structure. However, crops species such as millet (Echinochloa esculenta), lucerne (Medicago sativa) and saltbush (Atriplex nummularia) reduced the build-up of sodium in the soil. The results suggest that sodium was mainly removed from the soil through plant-assisted leaching. Of the crops grown, lucerne showed the most promise because it improved the soil physical properties, is able to grow well in alkaline environments, is a popular fodder crop and can be harvested multiple times from a single stand. Brewery effluent is more suitable for soil production systems than hydroponic production systems because the soil was able to act as a buffer against the high pH of post-AD BE, whereas in a hydroponics systems the high pH reduced the availability of key minerals to plants. In conclusion brewery effluent contains sufficient plants nutrients to support the growth of cabbages, saltbush, lucerne and millet. However the sodium content of BE is a concern as it accumulates in the soil, and in the long-term it may lead to soil degradation. It is suggested that the brewery change the pH neutralising treatment of BE from sodium hydroxide to potassium hydroxide, or dolomitic lime (calcium and magnesium carbonate) because this would reduce the introduction of sodium into the system, and would increase the suitability of BE for crop production, given potassium and calcium are plant nutrients. The benefits of developing this nutrient and water resource could contribute to cost-reductions at the brewery, more efficient water, nutrient and energy management, create job opportunities with the potential of improving food security in the local community.
Keywords: Uncatalogued